Choroidal effusion: a rare and unusual complication of daratumumab. Issue 8 (1st August 2022) - Singh, Aditi; Bazzi, Talal; Lebovic, Daniel; Demirci, Hakan
Abstract : Daratumumab-containing regimens are an effective treatment for advanced cases of multiple myeloma. Overall, daratumumab has a favourable safety profile, although rare side effects can occur. Rare side effects of daratumumab include choroidal effusion. Patients who begin to experience symptoms such as eye swelling, vision changes, eye discharge and blurry vision should undergo urgent ophthalmological evaluation and their daratumumab infusions held.